COST-EFFECTIVENESS OF METFORMIN-GLIMEPIRIDE COMBINATION COMPARED TO SINGLE METFORMIN USE IN DECREASING 2 H POST PRANDIAL BLOOD GLUCOSE - FITRIA, NAJMIATUL; ANDELA, MILA; RERITA, RESNA; NASIF, HANSEN (International Journal of Applied Pharmaceutics, 2024)
Objective: Complications related to diabetes could reduce the quality of life. In Indonesia, the costs incurred for diabetes mellitus annually will increase as complications of the disease increase. This study explored the cost-effectiveness therapy of metformin-glimepiride combination on post-prandial blood glucose. Methods: Glimepiride is added to the first category for diabetes mellitus receiving metformin to improve blood sugar levels and reduce costs. An observational study was conducted retrospectively to analyze post-prandial blood sugar levels with the total direct medical costs at Universitas Andalas Hospital. The study involved 114 medical records of patients referred during 2021. The combination of Metformin HCL and Glimepiride was compared to Metformin alone in measuring cost and effect parameters. The categorical dependent-independent groups were statistically analyzed using Chi-square, while the cost and effect parameters were calculated to get the Incremental Cost-Effectiveness Ratio (ICER) value. Results: There were no significant differences between groups on sociodemographic characteristics (p<0.05). An incremental cost value of IDR 43,291 was obtained for reducing post-prandial blood sugar by 21.92 mg/dl. Conclusion: Increasing cost and effect parameters require further analysis to determine the trade-off point.